عورتوں کو کتابت سکھانے کی ممانعت کا مسئلہ :حدیث"لاتعلموهن الکتابة" کا مطالعہ (Al-Qamar, 2020)
Islam is alleged of forbidding women from learning to write. It is said that a Ḥadīth from ʻA’isha says: "Don't teach women to write." This article explores the authenticity and correct context of the mentioned Ḥadīth. The gist of this article is that the ḥadīth referred is not worthy of argument regarding the under discussion issue. All the Muḥaddithīn except Imam Ḥākim agree that this narration is invalid, and Imam Ibn Jawzī has expressed surprise about the negligence of Imam Ḥākim in this regard. Moreover, there are separate ḥadīths on the justification of women learning to write, one of which is narrated from ʻA’isha, who is also the narrator of the under discussion ḥadīth. Imam Balādharī has mentioned from his chain of transmission, the names of five early Muslim women who knew how to write. Many great Muḥaddithīn and jurists have also explained the legitimacy of teaching women to write.
Keywords: Writing; Ḥadīth; analysis